Integrated Smart Irrigation System For Okra Plant - Koh, Yeong Cherng (2022)
Water is a necessary component of all life on Earth, including crops. The amount of water contained in crops ranges from 80 to 90 percent, indicating the importance of water to all life on Earth. However, the global population keeps increasing and cities have a larger population density than rural regions. Because of the growing pace of urbanization, more than half of the world's population will be living in cities by 2050. The correlation between water and agriculture is vital since it is required for crop development, which is necessary for food security. Roof planting, greenhouse farming, and other urban agricultural activities are the most common types of planting or farming in cities. Those who do not devote enough time to farming will see their crops suffer from a lack of water and nutrients because this manual technique needs more time spent monitoring and watering the crops. As a consequence, smart irrigation systems may be utilized in agriculture to minimize the amount of monitoring and watering required. To assess soil conditions, the smart irrigation system will include sensors such as an NPK sensor, a pH sensor, and a soil moisture sensor. If the soil lacks water, the smart irrigation system will pump water and irrigate the crops until the level is reached. If the nutrient and pH ranges are out of range, the smart irrigation system will alert the plant to be fertilized and will neutralize the crops. This smart irrigation system aims to reduce electricity consumption by utilizing a solar panel. The goal of this research is to determine how efficient and intelligent irrigation systems will be in the agricultural business in the future.